YAC Protocols - Markie, David. (Methods in Molecular Biology,, 1996)
Yeast artificial chromosomes (YACs) have their origins in the molecular genetic analysis of the yeast Saccharomyces cerevisiae. The construction of self-maintaining genetic elements from isolated frag ments of the yeast genome defined DNA sequences necessary for chro mosome function has provided telomeres, centromeres, and autonomous replicating sequences. In 1987 a reversal of the strategy put these short functional DNA sequences to work in cloning vectors, producing "yeast" chromosomes largely composed of foreign DNA. Initially the insert size of clones averaged several hundred kilobasepairs, a remarkable achieve ment. Rapid progress with cloning technology has since enabled the construction of YAC libraries with average insert sizes of around 1 Mb, with many clones exceeding that size, and YACs remain the largest capacity microbiological cloning system available. They effectively bridge the size gap between bacterial cloning (plasmids, cosmids, PI, and bacterial artificial chromosomes) and what could be considered mammalian cloning systems (somatic cell hybrids and irradiati- fusion gene transfer hybrids). YACs also brought with them a conceptual revolution in the man agement of clone libraries. The large carrying capacity of YACs, with subsequent reduction in the total number required, meant that it was conceivable to store clones individually rather than as pools that require constant re-plating. Each clone in the library has a unique address and, with successive screenings, information accumulates about individual clones.